2016
DOI: 10.1186/s40064-016-3257-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and molecular characterization of dengue viruses imported into Guangzhou during 2009–2013

Abstract: BackgroundDengue virus causes one of the most significant infectious diseases in tropical and subtropical regions, notable number of which is imported into China every year.ResultsIn this study, the molecular epidemiologic and phylogenetic analyses of dengue cases imported into Guangzhou in South China during 2009–2013 were conducted. During that period, 46 imported dengue cases were identified, including four serotypes. Most of the dengue patients were travelling from Southeast Asia, South Asia and Africa. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Our study further con rms the reports that the major epidemics thought to be dengue, emanated from three continents: Asia, Africa, and North America (42). There is a sudden increase in the number of imported DENV cases worldwide due to globalization (41). Adamawa is a state in Nigeria, a country located in West Africa region and shares a porous border with many African countries and accelerated in global trade and bilateral exchange program with many Asian countries such as China, India, Philippines, Malaysia, and Dubai.…”
Section: Discussionsupporting
confidence: 87%
“…Our study further con rms the reports that the major epidemics thought to be dengue, emanated from three continents: Asia, Africa, and North America (42). There is a sudden increase in the number of imported DENV cases worldwide due to globalization (41). Adamawa is a state in Nigeria, a country located in West Africa region and shares a porous border with many African countries and accelerated in global trade and bilateral exchange program with many Asian countries such as China, India, Philippines, Malaysia, and Dubai.…”
Section: Discussionsupporting
confidence: 87%
“…These results show that for more than ten years, there has been a rapid turnover of clusters of DENV-1 genotype I isolates due to probable multiple introductions in the Lao PDR from neighboring countries following the trend of this DENV-1 pattern at the regional level [15,16,18,29,[36][37][38]. The new genetic data also allows access to a deeper level of analysis of DENV through the clusters' dynamics.…”
Section: Discussionmentioning
confidence: 79%
“…All DENV-1 isolates detected in this study belonged to genotype I, which was first documented in Thailand in 1981 43 . Since that time, DENV-1 genotype I has been routinely isolated in Thailand and several other countries in Southeast Asia 44 , 45 . Interestingly, our DENV-1 phylogenetic tree showed that previous and present genotype I Thai strains did not cluster in the same clade.…”
Section: Discussionmentioning
confidence: 99%